Indonesia's Struggle For Democratic Resilience: Issues and Institutional Reforms - Mi’rojul Huda; Mubarok Muharam; Mochamad Arif Affandi; Agus Satmoko Adi; Silkania Swarizona; Eko Satriya Hermawan (International Journal of Law and Society, 2025)
Indonesia's democracy, despite over two decades of progress since the fall of the New Order regime, has faced stagnation and democratic backsliding in recent years. Indicators from institutions such as the Economist Intelligence Unit (EIU), Freedom House, and Varieties of Democracy (V-Dem) consistently highlight a decline in democratic quality. Contributing factors include identity politics, declining electoral integrity, political dynasties, and weak institutional capacities, described as "Low-Capacity Democracy." This study employs a qualitative approach to explore these challenges, including literature reviews, document analysis, and interviews. The findings reveal systemic issues at both institutional and societal levels, including weakened oversight bodies like the Corruption Eradication Commission (KPK), the dominance of executive power, and the rise of transactional politics and political dynasties. Digital challenges, such as disinformation and low digital literacy, also exacerbate these issues. This study recommends comprehensive reforms, such as strengthening independent institutions, enhancing transparency in public fund management, and improving political education to reduce transactional practices. Digital media regulations and technology-based electoral monitoring are also proposed to increase transparency. By addressing these issues, Indonesia can reinforce democratic resilience and foster an inclusive, accountable political system.